The Effects of Provision of Instrumental, Emotional, and Informational Support on Psychosocial Adjustment of Involuntary Childless Women in Pakistan. (October 2021) - Iram, Anila; Mustafa, Mudasir; Ahmad, Saeed; Maqsood, Sidra; Maqsood, Fauzia
The objectives of the study are to investigate (i) the level of social support, social adjustment, and psychological adjustment; and (ii) the effects of social support (emotional, informational, and instrumental support) on social adjustment, psychological adjustment, and psychosocial adjustment among childless women. A total of 334 woman respondents were surveyed using a simple random sampling technique. Factor analysis, reliability analysis, confirmatory factor analysis, and multiple linear regression analysis were used to analyze the data. In the overall model, emotional support, instrumental support, and informational support were significantly associated with social adjustment. In addition, emotional support and instrumental support were significant with psychological adjustment. Furthermore, emotional support, instrumental support, and informational support were the predictors of psychosocial adjustment among childless women. This study contributed to the broader avenues of understanding social support such as husband, in-laws, friends, and relatives, and the accumulation of social support among the childless women in the patriarchal society. The findings highlighted the efficacy and utility of the centuries-old social institution of family as a major predictor of psychosocial support to the childless woman. It subsidized to the limited body of research on provision of social support and psychosocial adjustment among childless women in the patriarchal society.